2000
DOI: 10.1007/pl00006746
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of BCNU antitumor efficacy by 9-substituted O 6-benzylguanines. Effect of metabolism

Abstract: Metabolism of BGS and dBG to BG explains the unexpected high efficacy of these compounds in potentiating the antitumor activity of BCNU in the athymic mouse model. The faster and more effective suppression of tumor MGMT by dBG and its greater efficacy, as compared with BGS, also correlates with a more rapid accumulation of BG in blood after dBG than after BGS administration, which results in faster and complete suppression of MGMT in Daov xenografts. Thus, metabolism of dBG and BGS to BG appears to be the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We chose an interval of 6 h from drug infusion to obtaining the specimen since this was in the range of the optimal time course of AGT inhibition in most experimental studies (Kokkinakis et al, 1996). The prior report of BG inhibition of AGT in intracranial tumors used an 18-h interval from drug infusion to tumor resection (Friedman et al, 1998).…”
Section: Neuro-oncologymentioning
confidence: 99%
“…We chose an interval of 6 h from drug infusion to obtaining the specimen since this was in the range of the optimal time course of AGT inhibition in most experimental studies (Kokkinakis et al, 1996). The prior report of BG inhibition of AGT in intracranial tumors used an 18-h interval from drug infusion to tumor resection (Friedman et al, 1998).…”
Section: Neuro-oncologymentioning
confidence: 99%
“…The effectiveness of these guanosine derivatives results from their efficient cellular uptake and catabolism into O 6 -BG[79].…”
mentioning
confidence: 99%
“…The compound O 6 -benzylguanine (BG), for instance, is a DNA repair inhibitor that inactivates the enzyme MGMT (O 6 -methylguanine-DNA methyltransferase), involved in the removal of alkyl adducts from the O 6 -position of guanine (174). BG and its analogue O 6 -benzyl-2'-deoxyguanosine (dBG) (175) are both capable of potentiating the cytotoxic effects of chloroethylating agents, such as BCNU and CCNU in medulloblastoma tumor xenografts (176,177) and colon carcinoma cells (174). Another study has revealed that BG alone is capable of reducing the volume of pancreatic tumors in mice, besides sensitizing pancreatic cancer cells to gemcitabine (178).…”
Section: Dna Repair and Cancer Chemotherapymentioning
confidence: 99%